Programming of Renal Development and Chronic Disease in Adult Life - Lumbers, Eugenie R.; Kandasamy, Yoga; Delforce, Sarah J.; Boyce, Amanda C.; Gibson, Karen J.; Pringle, Kirsty G. (Frontiers in Physiology, 2020)
Chronic kidney disease (CKD) can have an insidious onset. There may be no overt symptoms of renal dysfunction until about two thirds or more of the nephrons have been destroyed and glomerular filtration rate (GFR) falls to below 25% of normal (often in mid-late life) (1). Once End Stage Renal Disease (ESRD) has been reached, survival depends on renal replacement therapy (RRT). CKD causes hypertension and cardiovascular disease; and hypertension causes CKD. Albuminuria is also a risk factor for cardiovascular disease. Insidious forms of CKD have their origins in fetal life. This review describes the mechanisms underlying the development of CKD in adult life that results from abnormal renal development caused by an adverse intrauterine environment. The basis of this form of CKD is thought to be mainly due to a reduction in the number of nephrons formed in utero and the development of intraglomerular hypertension, which leads to glomerulosclerosis and ESRD. Factors that affect the risk of reduced nephron formation during intrauterine life are discussed and include maternal nutrition (malnutrition and obesity), smoking and alcohol, use of drugs that block the maternal renin-angiotensin system, vitamin A deficiency, glucocorticoid excess and maternal renal dysfunction. Since CKD, hypertension and cardiovascular disease add to the disease burden in the community we recommend that kidney size at birth should be recorded using ultrasound and those individuals who are born premature or who have small kidneys at this time should be monitored regularly by determining GFR and albumin:creatinine clearance ratio. Furthermore, public health measures to reduce obesity and diabetes mellitus in the community should be actively encouraged.